1995
DOI: 10.1063/1.359543
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of deep levels correlated with iron in silicon metal-oxide-semiconductor structure

Abstract: Thermal behavior of deep levels correlated with iron in Si MOS (metal-oxide-semiconductor) structure has been studied by isothermal capacitance transient spectroscopy. As a result, it is shown that interstitial iron scarcely affects the interface trap (Nt) of MOS structure. This is made clear by measuring Nt of Si MOS diodes containing iron impurity, the interstitial component of which is controlled by low temperature annealings. In addition, the low temperature (400 °C) annealing decreases interstitial iron c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In order to shed more light on the existence and role of Fe i defects, we proceeded to undertake additional heat treatments of the R sample consisting of successive reannealing at 210, 400 and 1200 • C before slow cooling. The first two temperatures were chosen with the intention of comparing the behaviour of our R sample to that of a similar one in the recent work of Kishino et al [21], whereas re-annealing at 1200 • C and subsequent slow cooling aim at the reproduction of the treatment of the S sample. We found that the number of recombination centres starts to decrease after annealing at T > 400 • C, in good agreement with the results of Kishino et al [21] who reported the disappearance of Fe i after treatment above 400 • C. On the other hand, the EBIC profile recorded after re-annealing at 1200 • C and subsequent slow cooling (curve c in figure 5) is almost identical to the analogous one scanned on the original S sample (figure 2 curve a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to shed more light on the existence and role of Fe i defects, we proceeded to undertake additional heat treatments of the R sample consisting of successive reannealing at 210, 400 and 1200 • C before slow cooling. The first two temperatures were chosen with the intention of comparing the behaviour of our R sample to that of a similar one in the recent work of Kishino et al [21], whereas re-annealing at 1200 • C and subsequent slow cooling aim at the reproduction of the treatment of the S sample. We found that the number of recombination centres starts to decrease after annealing at T > 400 • C, in good agreement with the results of Kishino et al [21] who reported the disappearance of Fe i after treatment above 400 • C. On the other hand, the EBIC profile recorded after re-annealing at 1200 • C and subsequent slow cooling (curve c in figure 5) is almost identical to the analogous one scanned on the original S sample (figure 2 curve a).…”
Section: Resultsmentioning
confidence: 99%
“…The first two temperatures were chosen with the intention of comparing the behaviour of our R sample to that of a similar one in the recent work of Kishino et al [21], whereas re-annealing at 1200 • C and subsequent slow cooling aim at the reproduction of the treatment of the S sample. We found that the number of recombination centres starts to decrease after annealing at T > 400 • C, in good agreement with the results of Kishino et al [21] who reported the disappearance of Fe i after treatment above 400 • C. On the other hand, the EBIC profile recorded after re-annealing at 1200 • C and subsequent slow cooling (curve c in figure 5) is almost identical to the analogous one scanned on the original S sample (figure 2 curve a). Besides the significant improvement of the EBIC overall signal (curve c in figure 5), it is worth noting that I GB for the R sample, as well as for the corresponding reference sample, recovers approximately, after re-annealing, to the corresponding value in the slow cooling case (curves a and b in figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that iron impurity scarcely affects the interface traps in p-type silicon wafers [2]. This shows that the enhancement of the interface traps varies with the impurity element of the heavy metals.…”
Section: Influence Of Heavy Metal Impurities On Interface Trapsmentioning
confidence: 97%
“…At the same time, we ascertained that a gold impurity greatly enhanced the interface traps [1] and an iron impurity scarcely affected them [2]. It was also clarified that the enhancement of the interface traps varied with the impurity element among the heavy metals.…”
Section: Introductionmentioning
confidence: 97%